Relative Nature of Thai Traditional Music through its Tuning System - Nattapol Wisuttipat (IJCAS (International Journal of Creative and Arts Studies), 2015)
Thai traditional music exhibits number of relative characteristics, though many of them are not expressed explicitly but only demonstrated orally. Its tuning system, despite having been put through many scientific studies for decades, cannot be given the absolute pitch frequencies. It is therefore possible that the tuning system does not have any absolute pitch frequencies but possesses relative nature. This papers aims to present the historic background, characteristics, past, current practices of Thai traditional music’s tuning system and to put forward the theoretical idea of non-existence of absolute tuning frequency and that of relative nature of Thai traditional music’s tuning system. The data was collected from previous researches on Thai traditional music’s tuning system and from sample instruments. The latter was then compared to each other and analyzed with respect to the former. The preliminary results were that tuning system of Thai traditional music was in the form of seven-tone equal temperament without any sharps or flats. But practically, it was not exactly equal as musicians still prefer the traditionalbiased tunings which is believed to be more tuneful. Regarding the tuning practices, the tuning of Fine Arts Department are most dominating among several others. Even though, the tuning of Fine Arts Department measure from various sources are slightly different in terms of frequencies and intervals. It can be concluded that the tuning system of Thai traditional music does not rely on specific pitch frequency, but is relative to intervals and personal preferences and its absolute pitch frequency is yet to be established.